Evaluation of CFRP reinforced prestressed concrete beams for shear behavior - Abbas, Yassin (Kansas State University, 2022)
Fiber-reinforced polymer (FRP) can be effectively utilized in structures as rods, sheets, bars, and tendons due to its high strength-to-weight ratio, non-corrosiveness, non-magnetic properties, and its flexibility. FRPs include carbon fiber-reinforced polymers (CFRPs), aramid fiber-reinforced polymers (AFRPs), and glass fiber-reinforced polymers (GFRPs). Previous studies have investigated these materials under various load conditions and in a variety of structures, including prestressed concrete beams reinforced with CFRP, which has the highest tensile modulus out of all the FRP varieties. The increasing popularity of FRP as a reinforcement particularly as prestressing tendons in concrete structures is prompting research to more accurately predict the behavior of such structures under various types of loading and boundary conditions. Although many studies have investigated the flexural behavior of beams reinforced with FRP, few studies have focused on their complex shear behavior. Design guidelines in the U.S. such as ACI440.4R-04 and AASHTO 2018 have been published to support the design of structures using FRP. The objective of this thesis was to evaluate these guidelines for accuracy in predicting nominal shear capacity using prestressed concrete beams reinforced with CFRP. This study also aimed to offer alternative solutions to improve calculations of nominal shear capacity for prestressed beams reinforced with CFRP tendons.
Keywords: CFRP; Shear; Prestressed